The Effect of Health, Safety, Security, and Environment (HSSE) on Employee Performance at PT Pelabuhan Indonesia (Persero) Regional 2 Teluk Bayur with Job Satisfaction as an Intervening Variable - Hafid Gisen Parastra; Erni Masdupi (Pusat Publikasi Nusantara, 2026)
This study examines the effect of Health, Safety, Security, and Environment (HSSE) on employee performance at PT Pelabuhan Indonesia (Persero) Regional 2 Teluk Bayur, with job satisfaction as an intervening variable. Using a quantitative approach and the variance-based Structural Equation Modeling Partial Least Squares (SEM-PLS) method, data were collected via questionnaires from 150 permanent employees. The analysis included tests of convergent and discriminant validity, composite reliability, and hypothesis testing through path coefficients and bootstrapping. The findings show that Health and Safety, Security, and Environment each have a significant positive effect on employee performance (T-statistics > 1.96; P-values < 0.05). Job satisfaction also significantly influences employee performance and mediates the relationship between Health and Safety and employee performance. However, job satisfaction does not significantly mediate the relationships between Security and employee performance, nor between Environment and employee performance. The R-square value of 0.781 indicates that HSSE and job satisfaction explain 78.1% of the variance in employee performance, with the remainder attributable to factors outside the model. Overall, the results confirm that effective HSSE implementation enhances employee performance both directly and indirectly through increased job satisfaction. The study recommends that organizations strengthen safety culture, adopt technology-based security systems, foster a comfortable and environmentally friendly workplace, and attend to employees’ psychological well-being to sustainably improve job satisfaction and productivity.